Propuesta para mejorar la gestión de la calidad en los procesos de producción mediante la metodología kaizen en la empresa Finolac. - Pachacama Ricardo, Xavier Almachi (2021)
The project proposes to improve the characteristics of the production processes in the production of dairy products using the 5S methodology, it takes its name from the five Japanese words that begin with the letter S: Seiri (Classification), Seiton (Order), Seiso (Cleaning ), Seiketsu (Standardization) and Shitsuke (Discipline), which give the guidelines to implement and maintain a Quality Management system within the organization, achieving results in the short term, from which the foundations can be laid for improve quality, safety and work environment conditions. The objective of this work was to determine the current situation of Finolac company, with respect to these five principles, through the collection of information through interviews, evaluations and photographic records, therefore the necessary criteria and theoretical requirements were identified. For the 5S and quality management, the practice of this methodology in production processes was proposed through qualitative and quantitative, documentary-bibliographic and descriptive research, through techniques and diagrams such as: cause-effect diagram, ISHIKAWA, flow charts, etc. With the improvement proposal, it was possible to reduce downtime and also that by practicing this 5S methodology, the time invested in making yogurt and cheese can be improved; In addition, 5S instructions were made available, configured to improve the industrial development of the company, with this practice it is sought that the company obtains a proposal for continuous improvement, quality, safety and an optimal work environment to improve the dairy production processes, the beneficiaries The project will be directly the employees and the manager of the company, generating greater economic income in its production which improved the quality and control of the products, thus fulfilling the expected results.